ASSOCIATION OF THYROID DYSFUNCTION WITH DEVELOPMENT OF POLYCYSTIC OVARIAN SYNDROME AMONG REPRODUCTIVE AGE WOMEN OF SIALKOT, PAKISTAN - RASHEED , I; ASHRAF , S; SHAKEEL , Q; BUTT , LN; SHAHWAR , D; MURAD , MA; ISHAQ , HA (Biological and Clinical Sciences Research Journal, 2024)
Polycystic Ovary Syndrome (PCOS) is a prevalent hormonal disorder among women of reproductive age, often co-occurring with metabolic syndromes such as thyroid dysfunction. Understanding this association is crucial for addressing the broader reproductive and general health implications. Objective: This study aims to investigate the association between thyroid dysfunction and the development of PCOS in women of reproductive age in Sialkot, Pakistan. Methods: This prospective study was conducted from May 2023 to May 2024 at Civil Hospital, Sardar Begum Hospital, Cheema Family Hospital, and Waleed Hospital. A total of 100 females were included, divided into two groups: 50 in the control group (no disease) and 50 in the treatment group with both thyroid dysfunction and PCOS. Participants aged 23 to 45 were selected from medicine and gynecology wards. Blood samples were analyzed for thyroid function, and a comprehensive questionnaire was administered to assess the prevalence and characteristics of symptoms related to PCOS and thyroid dysfunction. Statistical analysis was performed using T-tests to compare mean values of Triiodothyronine (T3) and Thyroxine (T4) between groups. Results: The treatment group exhibited a significant prevalence of symptoms: 80% reported hirsutism, 92% had irregular menstrual cycles, 72% experienced weight gain, 60% suffered from hair loss, 76% had acne and high blood pressure, and 64% showed signs of Acanthosis nigricans. Significant differences in thyroid hormone levels were observed, with mean T3 levels at 9.4718 (SE = 1.7373, 95% CI [5.9783, 12.9653], T = 5.4525, p < 0.05) and mean T4 levels at 51.172 (SE = 6.7027, 95% CI [37.6952, 64.6508], T = 7.6333, p < 0.05) as compared to control group. Conclusion: The findings highlight a significant association between thyroid dysfunction and PCOS, with thyroid dysfunction impacting T3 and T4 levels in patients with PCOS. This underscores the need for targeted thyroid screening in PCOS patients to manage and mitigate the broader health implications effectively.